A Systematic Review of Systematic Reviews on Open Educational Resources: An Analysis of the Legal and Technical Openness - Sousa, Lorena; Pedro, Luís; Santos, Carlos (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2023)
Almost all open educational resources (OER) definitions encompass key concepts such as the 5R activities and open licenses. However, little attention is given to the technical aspects and tools that allow the user to interact with these resources. This study aims to answer five research questions regarding (a) 5R activities, (b) open licenses and intellectual property, (c) technical aspects, (d) tools for developing OER, and (e) the topic of sustainability. To answer these questions, a systematic review of systematic reviews on OER was conducted following the reporting checklist of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Sixteen studies were eligible and included in this review. The main findings suggest that although most studies did not mention the term 5R exactly, they mentioned related terms, such as share and adaptation. There was also a tendency toward focusing on more legal issues than technical aspects. Besides, most of the studies that mentioned tools discussed them as platforms to access OER, not exactly tools that encourage users to develop or adapt resources in an easy way. In relation to sustainability, several studies highlighted the relevance of developing sustainable OER models, but only a few suggested approaches to sustain an OER project. Therefore, with this article, we hope to raise awareness of the importance of the technical openness and tools that might contribute to fostering users’ engagement with the OER, helping them to act as producers and contributors rather than mere passive receivers.